Thermal Acclimation of Foliar Carbon Metabolism in Pinus taiwanensis Along an Elevational Gradient - Lyu, Min; Sun, Mengke; Peñuelas, Josep; Sardans, Jordi; Sun, Jun; Chen, Xiaoping; Zhong, Quanlin; Cheng, Dongliang (Frontiers in Plant Science, 2022)
Climate change could negatively alter plant ecosystems if rising temperatures exceed optimal conditions for obtaining carbon. The acclimation of plants to higher temperatures could mitigate this effect, but the potential of subtropical forests to acclimate still requires elucidation. The methods of the spatial-temporal substitution to determined the photosynthetic and respiratory-temperature response curves, optimal temperature of photosynthesis (Topt), photosynthetic rate at Topt, sensitivity temperature (Q10), and the rate of respiration at a standard temperature of 25 °C (R25) for Pinus taiwanensis at five elevations (1200, 1400, 1600, 1800, and 2000 m) in two seasons (summer and winter) in the Wuyi Mountains in China. The response of photosynthesis in P. taiwanensis leaves to temperature at the five elevations followed parabolic curves, and the response of respiration to temperature increased with temperature. Topt was higher in summer than winter at each elevation and decreased significantly with increasing elevation. Q10 decreased significantly with increasing elevation and was also affected by season and the interaction between season and elevation. These results showed a strong thermal acclimation of foliar photosynthesis and respiration to current temperatures across elevations and seasons, and that R25 increased significantly with elevation and were higher in winter than summer at each elevation indicating that the global warming can decrease of R25. These results strongly suggest that this thermal acclimation will likely occur in the coming decades under climate change, so the increase in respiration rates of P. taiwanensis in response to climatic warming may be smaller than predicted and thus may not increase atmospheric CO2 concentrations.